2020
DOI: 10.1111/ecc.13360
|View full text |Cite
|
Sign up to set email alerts
|

Electronic von Frey as an objective assessment tool for oxaliplatin‐induced peripheral neuropathy: A prospective longitudinal study

Abstract: Objective There is wide discrepancy on how to perform clinical assessment of oxaliplatin‐induced peripheral neuropathy. In this scenario, the Electronic von Frey (EVF), which evaluates pain objectively based upon mechanical pain thresholds (MPTs), may be a valuable tool. The present study aims to quantify hyperalgesia in the hands and feet of patients treated with oxaliplatin and to propose a novel method to classify the degree of neurotoxicity using EVF‐derived measures as cut‐off points. Methods This is a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Chronic oxaliplatin-induced peripheral neuropathy was assessed with a Von Frey Test [ 33 , 54 , 55 ]. The Von Frey test assesses chronic hypoesthesia induced by oxaliplatin peripheral neuropathy.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic oxaliplatin-induced peripheral neuropathy was assessed with a Von Frey Test [ 33 , 54 , 55 ]. The Von Frey test assesses chronic hypoesthesia induced by oxaliplatin peripheral neuropathy.…”
Section: Methodsmentioning
confidence: 99%
“…The situation in stage III appears more complex. In a study on patients included in a randomized trial on adjuvant 5-FU plus Oxaliplatin and folinic acid (FOLFOX) after resection of stage III CRC, Sinicrope et al found that KRAS and BRAF mutations had a negative prognostic effect on disease-free survival, while MSI was not prognostic in all patients but significantly interacted with the tumor site and nodal status [78]. Accordingly, only patients with right-sided MSI CRC had a better outcome, and such an advantage was lost in those with N2 tumors [78].…”
Section: Predictive Value Of Msimentioning
confidence: 99%
“…Quantitative sensory testing (QST) examines subjective sensory function by measuring the abnormal detection and pain thresholds to several sensory modalities. The usefulness of these non-invasive psychophysical measurements in the clinic setting for detecting subclinical neurologic changes early on to identify patients that will experience OXAIPN has been largely explored [12,20,20,42,51,53,54,56,[75][76][77][78][79][80][81][82].…”
Section: Quantitative Sensory Tests (Qst)mentioning
confidence: 99%
“…Quantitative sensory testing (QST) examines subjective sensory function by measuring the abnormal detection and pain thresholds to several sensory modalities. The usefulness of these non-invasive psychophysical measurements in the clinic setting for detecting subclinical neurologic changes early on to identify patients that will experience OXAIPN has been largely explored [ 12 , 20 , 20 , 42 , 51 , 53 , 54 , 56 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 99%
“…Touch threshold changes became statistically significant in the fingertips at middle and 8 chemotherapy doses [ 42 ] whereas these findings only occurred after treatment completion in Kroigard’s study [ 60 ]. Very recently, electronic von Frey anaesthesiometer, which evaluates hyperalgesia based upon mechanical pain thresholds (MDTs), was tested prospectively in 46 CRC patients treated with OXA, and showed a decrease of 40 g in the MDT of both hands and feet as cut-off for diagnosing grade 2 or 3 OXAIPN with a total accuracy of 84.2% and 81.6% in hands and feet, respectively [ 78 ]. Besides diagnostic utility, the role MDT changes for predicting OXAIPN requires further research.…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 99%